Ongoing supervision as a method to implement Motivational interviewing: Results of a randomized controlled trial. Issue 8 (August 2021) - Beckman, Maria; Lindqvist, Helena; Öhman, Lina; Forsberg, Lars; Lundgren, Tobias; Ghaderi, Ata
Highlights: MI skills of practitioners with previous MI trainings were evaluated. The practitioners received either individual or group subsequent supervision. The group supervision and the individual supervision were equally effective. Objective feedback did not disturb the working alliance or cause supervisee anxiety. Objective feedback based on fewer variables did not promote skill acquisition. Abstract: Objective: To assess skills in Motivational interviewing (MI) at the Swedish National Board of Institutional Care (SiS), and to evaluate different ways to provide MI supervision. Methods: SiS practitioners ( n = 134) were randomized to regular group supervision, or individual telephone supervision based on only the behavioral component of a feedback protocol, or the full protocol. Participant's mean age was 43.2 ( SD =10.2), and the majority (62.7%) were females. Results: Many participants showed beginning proficiency already at baseline, indicating a successful implementation. Still, results varied widely. The regular supervision and the supervision based on objective feedback were equally effective, and the group receiving feedback based on fewer variables of the protocol performed better on only one of the seven skill measures. The objective feedback did not provoke supervisee discomfort/distress, or negatively affect the supervisory relationship. Conclusions: Extensive MI implementation can increase practitioners' skills in MI, but the question of the best mode of ongoing supervision needs further attention. Practice Implications: Objective feedback does not seem to negatively affect the supervisee's skill acquisition or the supervisor-supervisee working alliance, but the question of how to most efficiently provide feedback from multifaceted feedback tools remains unanswered.